A Developmental Perspective on Children With Incarcerated Parents. (17th November 2020) - Poehlmann‐Tynan, Julie; Turney, Kristin
Abstract: Parental incarceration is a socially relevant topic with substantial implications for children, yet it is understudied by child development scholars. About 2.6 million U.S. children currently have a parent who is incarcerated, and by age 14, one in 14 U.S. children experiences a resident parent leaving for jail or prison. In this developmentally oriented review, we summarize research on associations between parental incarceration and child well‐being, and suggest areas where developmental scientists can contribute. While most analyses of large population‐based U.S., datasets have found that experiencing paternal incarceration typically has detrimental implications for child well‐being, especially as children grow older, analyses of maternal incarceration have yielded less consistent findings. Longitudinal population‐based developmental studies focusing on parental incarceration, especially early in life through adulthood, are urgently needed to answer basic questions, clarify mixed findings, inform policies, and develop interventions for vulnerable children.